Pengaruh Pola Asuh Orang Tua Terhadap Kemandirian Anak Usia Dini - Osa Mahmudatunnisa; Nanda Maharani Tyas Tariza; Rohmah Dina Hanifah; Fidrayani Fidrayani (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Children's independence is an important character to be built from an early age and is influenced by parenting patterns. Parenting has an important role in shaping children's independence. This study aims to compare several aspects of research results between 2019 and 2024. This study used a Systematic Review or Systematic Literature Review (SLR) approach with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) method. The results showed that parenting has a significant influence on early childhood independence. Parenting that provides a combination of freedom clear boundaries, and balanced shows a fairly high correlation of 0.674 which indicates that it is very influential on children's independence. While the very low correlation result of 0.002 indicates that other factors that may be more dominant in influencing children's independence may play a greater role than parenting patterns.